Edukasi nutrisi dan kesadaran orang tua sebagai pilar pencegahan stunting di desa plaosan - mahsuni, intan sukma (Maliki Interdisciplinary Journal, 2025)
Stunting is a health problem caused by chronic nutritional disorders and recurrent infections. Stunting is a health problem that has recently been discussed frequently because of the impact and causes that directly plunder the community through their daily lives. The stunting rate in Indonesia has decreased considerably after being at a fairly high rate. Suppressing this stunting rate is a special task for the government in terms of health. With their service mission, UIN Malang students who are conducting Student Work Lectures take the initiative to hold a stunting prevention socialization in Plaosan Village. Wonosari District, Malang Regency. This program involves working with health workers and Posyandu cadres to educate parents and pregnant women about nutrition. The activities included nutrition counseling, distribution of brochures, and demonstration of affordable nutritious food. The positive response from the community demonstrates the importance of such initiatives in increasing awareness and practice of stunting prevention.